Are the Intracranial Lipomas Always Asymptomatic? - Yilmaz, Mustafa; Dinc, Aytac; Gurger, Mehtap; Atescelik, Metin (Derman Medical Publ, 2014)
Intracranial lipomas are rarely observed, and accepted as the congenital lesion of central nervous system. Intracranial lipomas are usually based centrally and have benign character. In the brain, it is mostly localized in pericallosal region, quadrigeminal system, and suprasellar region and cerebellopontine angles. As being mostly asymptomatic, the patients occasionally constitute clinical symptoms according to localization area. These symptoms are systemic symptoms such as cephalalgia, drowsiness, crisis and ataxy. In this article, we aimed to present the intracranial lipomas phenomenon which was diagnosed to have caused ptosis and upper lateral sight problem, namely causing localized neurological symptom, situated in mesencephalon and having pressure effect, regarding a 57-year old male patient brought to the emergency service with the nausea, throwing up and cephalalgia ailments.
Keywords: Intracranial Lipomas; Mesencephalon; Neurologic Deficit